If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -6y = 3 + -7y Solving 9 + -6y = 3 + -7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7y' to each side of the equation. 9 + -6y + 7y = 3 + -7y + 7y Combine like terms: -6y + 7y = 1y 9 + 1y = 3 + -7y + 7y Combine like terms: -7y + 7y = 0 9 + 1y = 3 + 0 9 + 1y = 3 Add '-9' to each side of the equation. 9 + -9 + 1y = 3 + -9 Combine like terms: 9 + -9 = 0 0 + 1y = 3 + -9 1y = 3 + -9 Combine like terms: 3 + -9 = -6 1y = -6 Divide each side by '1'. y = -6 Simplifying y = -6
| 3x+4=40 | | 5y+3=4y-6 | | x-6x+11+3x+4x-4=13+2.4 | | p+31=29 | | 5+13x=70 | | f-32=1.8c | | x+x+2+x+4=345 | | 5+13x=31 | | 2(m+7)=4(11-m) | | 11a-9+5a+26= | | x+3(x+2)=30 | | 9f+15=51 | | -5b-12=-2 | | 5k-(-7)=-7 | | 7y+5=-9 | | -20+4x=0 | | X-2y=10 | | 6x-x+9=19 | | 6x-x+9=19 | | 1+9x=57+x | | 5x-3=15x-43 | | 6x+38=16x-62 | | 9x-5=7x+5 | | 5(3x+8)=30 | | -4+2x=0 | | -4+2x=12 | | 5(2k+3)=36 | | 5(4y-1)=47 | | 4(6x+5)=10 | | 2a-b=1 | | 3(4t+5)=51 | | 3(4t-1)=78 |